Ethylene polymerization using N-Heterocyclic carbene complexes of silver and aluminum - Nanako Kimura; Daisuke Takeuchi; Sayoko Ogura; Ayaka Takazawa; Masaki Kakiage; Takeshi Yamanobe; Hiroki Uehara (Designed Monomers and Polymers, 2023)
Various transition metal catalysts have been utilized for ethylene polymerization. Silver catalysts have attracted less attention as the catalysts, but are potential for production of high molecular weight polyethylene. Herein, we report that silver complexes with various N-heterocyclic carbene (NHC) ligands in combination with modified methylaluminoxane (MMAO) afford polyethylene with high molecular weight (melting point over 140°C). SEM observation showed that the produced polyethylene has ultra-high molecular weight. NMR investigation of the reaction between the silver complexes with organoaluminums indicate that the NHC ligands transfer from the silver complex to aluminum to produce NHC aluminum complexes. Ph3C[B(C6F5)4] abstract methyl group from the NHC aluminum complex to afford cationic aluminum complex. The NHC aluminum complex promoted ethylene polymerization in the presence of Ph3C[B(C6F5)4] and organoaluminums. NHC ligand also promoted ethylene polymerization in combination with MMAO to produce polyethylene with high melting point (140.7°C). Thus, the aluminum complexes are considered to be the actual active species in silver-catalyzed ethylene polymerization.